Inbreeding studies in a quilombo isolate from the state of São Paulo - Lemes, Renan Barbosa (2017)
Endogamy levels are usually estimated using genealogical or molecular markers data. By means of both type of data from a traditional Brazilian tri-hybrid quilombo population aggregate (located at the Ribeira River Valley in the State of São Paulo), the aim of this work, using different methods, was to obtain reliable estimates of its average inbreeding coefficient, as well as to establish pertinent demographic inferences. The results we obtained are presented in three chapters. The first one, represented by the offprint of a published paper, deals with the estimation of the inbreeding coefficient using both a complete genealogical and comprehensive molecular information. F values were estimated for each community using all available pedigree information and averaging the inbreeding coefficients from all individuals represented in the genealogies. Molecular f values were estimated from the analysis of 30 highly heterogenous sets of molecular markers (14 biallelic SNPs and 16 multiallelic microsatellites), genotyped in different groups of individuals from the population. The second chapter (a research paper already published), presents a simplified method to estimate the variance of the inbreeding coefficient. The simple approximations we provided can be applied to a locus with any number of alleles, producing estimates fully validated by computer simulations. The last chapter is a manuscript yet to be published that deals with inbreeding and demographic inferences, obtained from the information of hundreds of thousands of biallelic SNP markers. A new manner to obtain estimates of Wright\'s fixation index f is presented, consisting in the use of the joint information of two sets of markers (one complete and another excluding markers in patent linkage disequilibrium). Quilombo demographic inferences were obtained by means of ROHs analyses, which were adapted to cope with a highly admixed population with a complex foundation history